Awareness That Breastfeeding Reduces Breast Cancer Risk: 2015–2017 National Survey of Family Growth. Issue 6 (December 2020) - Hoyt-Austin, Adrienne; Dove, Melanie S.; Abrahão, Renata; Kair, Laura R.; Schwarz, Eleanor Bimla
Abstract : Only 38.5% of U.S. women and female adolescents are aware that breastfeeding is associated with reduced incidence of breast cancer, and efforts are needed to educate pregnant patients about the maternal health benefits breastfeeding provides.